(untitled) (Colloquia Comparativa Litterarum, 2025)
The article problematises the connection between the verbal representation and the visual representation in the first Bulgarian edition of Inferno (1906). It aims to demonstrate that Gustavе Doré’s drawings, which illustrate Konstantin Velichkov’s translation, contribute to the better reception of Dante’s masterpiece. Thus, I will try to explore the relationship between the text and the iconic paratext, between the interlingual translation and the intersemiotic translation, by bringing out the empathy of the translator.